2020
DOI: 10.24996/ijs.2020.61.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiofilm Efficacy of Gold Nanoparticles Against Acinetobacter baumannii

Abstract: Acinetobacter baumannii is highly adapted to hospital environments, causing persistent chronic infections due to its ability to form biofilms. In this work, the antibiofilm activity of AuNPs with a subMIC concentration of 9.34 μg/ml was investigated by the microtiter plate method against 80 clinical isolates of A. baumannii. The results revealed that the biofilm was significantly (P< 0.05) reduced by 48.2 – 82.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The high prevalence of integron (class I) in A. baumannii isolates can be attributed to several factors, including inappropriate antibiotic use for A. baumannii infections, which leads to high expression of integrons (class I), and, secondly, the ability of integrons' to obtain new gene cassettes, which leads to antibiotic resistance spreading among clinical isolates. Furthermore, integrons Class 1 are more common than the other classes of integrons, presumably because they are found on genetic elements such as transposons and conjugative plasmids [21]…”
Section: The Results Of Integrons Detectionmentioning
confidence: 99%
“…The high prevalence of integron (class I) in A. baumannii isolates can be attributed to several factors, including inappropriate antibiotic use for A. baumannii infections, which leads to high expression of integrons (class I), and, secondly, the ability of integrons' to obtain new gene cassettes, which leads to antibiotic resistance spreading among clinical isolates. Furthermore, integrons Class 1 are more common than the other classes of integrons, presumably because they are found on genetic elements such as transposons and conjugative plasmids [21]…”
Section: The Results Of Integrons Detectionmentioning
confidence: 99%
“…Local studies showed that the sub-inhibitory concentrations of nanoparticles had an antibiofilm activity against Gram-negative bacteria. (Al-Khafaji, 2017, Al-Shaabani et al, 2020.…”
Section: Antimicrobial Activity Resultsmentioning
confidence: 99%
“…In light of the significant rise in biological and bacterial threats, particularly in sectors related to human consumption such as food, food packaging, and water, scientists are driven to create innovative inorganic nanoparticle substances with antibacterial properties. These substances are intended to be both user-friendly and devoid of any adverse side effects [15][16][17]. A discovery by scientists shows promise in the battle against antibiotic resistance by using a laser to trigger the bactericidal activity of AgNPs.…”
Section: Adhesion Aggregation Maturationmentioning
confidence: 99%